Fiscal Devaluation in a Monetary Union - Philipp Engler; Juha Tervala; Giovanni Ganelli; Simon Voigts (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Between 1999 and the onset of the economic crisis in 2008 real exchange rates in Greece, Ireland, Italy, Portugal and Spain appreciated relative to the rest of the euro area. This divergence in competitiveness was reflected in the emergence of current account imbalances. Given that exchange rate devaluations are no longer available in a monetary union, one potential way to address such imbalances is through a fiscal devaluation. We use a DSGE model calibrated to the euro area to investigate the impact of a fiscal devaluation, modeled as a revenue-neutral shift from employers social contributions to the Value Added Tax. We find that a fiscal devaluation carried out in Southern European countries has a strong positive effect on output, but a mild effect on the trade balance of these countries. In addition, the negative effect on Central-Northern countries output is weak.
Keywords: E32; E62; F32; 330